ALPOMISH VA KUNTUG’MISH DOSTONLARI ASOSIDA KOMPLEKS ETNOTURIZM MAHSULOTINI YARATISH HAMDA UNI XALQARO BOZORGA EKSPORT QILISHNING NAZARIY TAHLILI - TILOVMURODOV SHOHJAHON, (TADQIQOTLAR, 2026)
Abstarct:  This  study  provides  an  in-depth  analysis  of  the  theoretical, institutional,  and  economic  mechanisms  for  developing  a  comprehensive ethnographic  tourism  product  based  on  epic  narratives  and  exporting  it  to  the international market.